2018
DOI: 10.1080/07434618.2018.1506823
|View full text |Cite
|
Sign up to set email alerts
|

The effects of explicit instruction in academic vocabulary during shared book reading on the receptive vocabulary of children with complex communication needs

Abstract: The purpose of this study was to evaluate the effect of explicit vocabulary instruction during shared reading experiences on the acquisition of receptive academic vocabulary for children with complex communication needs. A single-subject, multiple-probe design was used. Three preschool-aged children (i.e., one with autism spectrum disorder, one with developmental delay, and one with a rare genetic disorder) were each taught two sets of vocabulary words. Intervention consisted of explicit vocabulary instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Language production skills were most frequently targeted ( n = 19), followed by studies targeting both language comprehension and production ( n = 18). Two studies (Grela & McLaughlin, 2006; Yorke et al, 2018) targeted language comprehension alone ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Language production skills were most frequently targeted ( n = 19), followed by studies targeting both language comprehension and production ( n = 18). Two studies (Grela & McLaughlin, 2006; Yorke et al, 2018) targeted language comprehension alone ( n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Parent-led SBR has become part of the daily routine for many families with recognized benefits in cognition, language and literacy development (Burgoyne & Cain, 2020;Cutler & Palkovitz, 2020). Clinician-led SBR may be used as part of an intervention session to explicitly target a child's language or literacy skills (Kaderavek et al, 2002;Yorke et al, 2018). Arciuli et al (2013) explored SBR between mothers and their children with autism and found that mothers corrected print-based errors more frequently than they provided contextual information to support reading comprehension during SBR.…”
Section: Shared Book Readingmentioning
confidence: 99%
“…Meanwhile, Yorke et al (2018) examined the influence of explicit vocabulary teaching on the acquisition of receptive academic vocabulary for children with complex communication needs over the course of many shared reading sessions. Autism spectrum condition, developmental delay, and a unique genetic disorder are among the complicated communication demands.…”
Section: Literature Reviewmentioning
confidence: 99%